Characteristics of the Bacterial Community in Alpine Meadows in Response to Altitude and Aspect in the Qilian Mountains, Northwest China - Qiang Li; Ying Zhang; Xiaoni Liu; Fan Yang (Ecology and Evolution)
ABSTRACT As one of the most sensitive and fragile alpine ecosystems in the Qilian Mountains, the alpine meadow holds significant scientific importance in understanding the changes in the characteristics of soil bacterial community in response to altitude and aspect variations. In our study, we analyzed the composition, diversity, and function of soil bacterial communities in alpine meadows at different altitudes and aspects and their relationship with environmental factors. Our results indicate that altitude and aspect orientation significantly influences the diversity index and composition of soil bacterial communities. Specifically, the Shannon and Chao1 indices of soil bacteria initially increased and then decreased with increasing altitude, with the Shannon index being lower in shady aspects compared to sunny aspects, and the Chao1 index being lower in sunny aspects above an altitude of 3400 m compared to shady aspects at the exact altitudes. Using Linear Discriminant Analysis Effect Size analysis, we identified 77 bacterial species in the research area, with key ecological functions primarily associated with nitrification, aerobic ammonia oxidation, and chitinolysis. Furthermore, we found that soil water content and Urease were the main factors influencing bacterial community composition. Our findings underscore the significant impact of altitude orientation on bacterial communities in alpine grasslands, emphasizing the importance of considering bacterial differences in evaluating alpine grassland health.